2022
DOI: 10.20944/preprints202202.0113.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delineating the Tissue-Mediated Drought Stress Governed Tuning of Conserved miR408 and Its Targets in Rice

Abstract: MicroRNAs act as the cardinal post-transcriptional monitors of gene regulatory networks sculpturing the developmental plasticity and stress responses in plants. Single miRNA target several genes and how the transcriptional regulation of miRNA impacts its pool of targets in different tissues and stress conditions is still elusive. The present study investigated the highly conserved and evolving MIR408 family comprehensively by redefining its evolutionary conservation and diversification in plants followed by de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In chickpea, increased drought tolerance was achieved by overexpression of miR408 [80], which in turn is known as environmental regulator in a variety of stresses such as dehydration [87,90,32], and mechanical stress [91], and reactive oxygen species [92]. In line with this study, recently Balyan et al [99] found that overexpression of miR408 in drought-sensitive rice enhances photosynthetic parameters such as electron transport rate (ETR) and effective photochemical quantum yield of photosystem II (Y(II)) and water scarcity tolerance. Additionally, the function of miR408 in drought-stress tolerance has been recently validated in cowpea seedlings, where overexpression of miR408 result in enhanced drought and salinity tolerance in transgenic lines compared to the wild type [100].…”
Section: Functional Identification Of Drought-stress Responsive Mirnassupporting
confidence: 69%
“…In chickpea, increased drought tolerance was achieved by overexpression of miR408 [80], which in turn is known as environmental regulator in a variety of stresses such as dehydration [87,90,32], and mechanical stress [91], and reactive oxygen species [92]. In line with this study, recently Balyan et al [99] found that overexpression of miR408 in drought-sensitive rice enhances photosynthetic parameters such as electron transport rate (ETR) and effective photochemical quantum yield of photosystem II (Y(II)) and water scarcity tolerance. Additionally, the function of miR408 in drought-stress tolerance has been recently validated in cowpea seedlings, where overexpression of miR408 result in enhanced drought and salinity tolerance in transgenic lines compared to the wild type [100].…”
Section: Functional Identification Of Drought-stress Responsive Mirnassupporting
confidence: 69%
“…miR408 is a multistress-responsive miRNA that observed to be differentially regulated in plants such as Arabidopsis (Song et al, 2017), Triticum (Feng et al, 2013), Oryza (Balyan et al, 2022), Chickpea (Hajyzadeh et al, 2015), and Vigna unguiculata (Mishra et al, 2021). Previous studies showed that overexpression of miR408, by downregulation of the direct target genes, obviously promotes photosynthetic activity, biomass, and seed yield (Song et al, 2017;Pan et al, 2018), as well as tolerance to drought stress (Hang et al, 2021).…”
Section: Mirna-mrna Network Under Drought Stress In Camellia Oleiferamentioning
confidence: 99%